New ecological notes on the freshwater chrysophycean alga Hydrurus foetidus (Chrysophyceae, Heterokontophyta): a study from Serbia (Southeast Europe) - Rakonjac Aleksandra B.; Simić Snežana B. (Oceanological and Hydrobiological Studies)
Hydrurus foetidus (Chrysophyceae, Ochrophyta) is a freshwater benthic alga that appears as a mucilaginous, filamentous thallus. It is geographically widespread but restricted to cold waters, with optimal temperatures for growth between 2°C and 12°C. The lethal temperature for this alga is 16°C. This paper reports the second occurrence of H. foetidus in waters with temperatures much above the recorded lethal temperature. In addition, we describe the non-obligate Hydrurus–Paralemanea association for the first time, with Paralemanea being a substrate for Hydrurus growth. This non-obligate association may be a strategy for the species’ survival during the summer season or the species’ response to climate change. Furthermore, we present co-occurring macroalgae, with special emphasis on the first finding of the rare freshwater chrysophycean alga Phaeodermatium rivulare in Serbian aquatic ecosystems.